Comparative Analysis of a Building Frame Under Dynamic Loading Considering Post Tensioning Members at the Edges Using Staad.Pro - Alam, Md Sarfaraz; Gabbi, Raviraj Singh; Tembhre, Vijay (International Journal of Scientific Research in Civil Engineering, 2021)
The modern era construction has led to the use of post-tensioning method in every projects whether commercial or residential sectors. Looking over the flaws of the conventional method of construction, post-tensioning being an upgrade can overcome the deficiencies of the conventional method of construction, for example, more slender structural members, lighter in weight and smaller floor-to-floor heights. Post-tensioning assures every plan to quite economical and safe. The experimental results on the seismic behaviour of post-tensioned high rise G+20 structure with the bonded system is compared. A Symmetrical arrangement of (G+20) floors is been considered in this comparative analysis considering Pushover Analysis for Zone V according to I.S. 1893 section 1 2016. The analytical tool Stadd.Pro structural programming is been used for the designing and analysis of the case study on the parameters namely maximum storey displacement, axial forces, shear forces, maximum bending, storey drift, displacement in x and z direction and Quantity examination and costing. The Analysis results demonstrated the stability of the Post-tensioned Structure as far as resisting against seismic forces against the corners of the structure. Regarding cost, we have observed that the Post Tensioning structure edge was discovered 30% not exactly uncovered casing structure.